Best practices for outsystems development and Its influence on test automation - Salgueiro, Joana (2021)
Low-code development platforms are designed to accelerate software development with a minimum of hand coding. They have allowed professionals with distinct backgrounds to become software developers. This brings more professionals to IT areas, reskilling some of them from different areas of knowledge but, at the same time, it has also brought to the software development area many professionals without a strong background in this area. Although testing should be performed in all applications, regardless of the programming language or the platform used, this reinforces the need for testing low-code developed applications. In this work, we study the test automation process on the OutSystems low-code development platform. The focus is on Unit, Integration/API and System/End-to-End testing levels. Examples illustrate that the implementation of best practices during the development process can have a significant influence on the test automation process. However, it is important to know whether the workload associated with the implementation of the best practices can undermine the benefits of using a low-code platform and it is important to consider that not all test automation tools have the same behavior.